Cardiac stereotactic body radiotherapy to treat malignant ventricular arrhythmias directly affects the cardiomyocyte electrophysiology - Mages, Christine; Gampp, Heike; Rahm, Ann-Kathrin; Hackbarth, Juline; Pfeiffer, Julia; Petersenn, Finn; Kramp, Xenia; Kermani, Fatemeh; Zhang, Juan; Pijnappels, Daniel A.; de Vries, Antoine A. F.; Seidensaal, Katharina; et al. (Heart rhythm, 2024)
Background - Promising as a treatment option for life-threatening ventricular arrhythmias, cardiac stereotactic body radiotherapy (cSBRT) has demonstrated early antiarrhythmic effects within days of treatment. The mechanisms underlying the immediate and short-term antiarrhythmic effects are poorly understood. - Objective - We hypothesize that cSBRT has a direct antiarrhythmic effect on cellular electrophysiology through reprogramming of ion channel and gap junction protein expression. - Methods - After exposure to 20 Gy of x-rays in a single fraction, neonatal rat ventricular cardiomyocytes were analyzed 24 and 96 hours postradiation to determine changes in conduction velocity, beating frequency, calcium transients, and action potential duration in both monolayers and single cells. In addition, the expression of gap junction proteins, ion channels, and calcium handling proteins was evaluated at protein and messenger RNA levels. - Results - After irradiation with 20 Gy, neonatal rat ventricular cardiomyocytes exhibited increased beat rate and conduction velocity 24 and 96 hours after treatment. Messenger RNA and protein levels of ion channels were altered, with the most significant changes observed at the 96-hour mark. Upregulation of Cacna1c (Cav1.2), Kcnd3 (Kv4.3), Kcnh2 (Kv11.1), Kcnq1 (Kv7.1), Kcnk2 (K2P2.1), Kcnj2 (Kir2.1), and Gja1 (Cx43) was noted, along with improved gap junctional coupling. Calcium handling was affected, with increased Ryr2 ryanodin-rezeptor 2 and Slc8a1 Na+/Ca2+ exchanger expression and altered properties 96 hours posttreatment. Fibroblast and myofibroblast levels remained unchanged. - Conclusion - cSBRT modulates the expression of various ion channels, calcium handling proteins, and gap junction proteins. The described alterations in cellular electrophysiology may be the underlying cause of the immediate antiarrhythmic effects observed after cSBRT.